1999
DOI: 10.1038/sj.onc.1202624
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 over-expression in prostate cancer is associated with decreased patient survival and persists in androgen independent disease

Abstract: Identification of prostate cancers at high risk of progression is difficult and a better understanding of how peptide growth factors influence cellular function might be useful. Fibroblast growth factors (FGFs) have been implicated in prostate cancer development. FGF8 was identified in the Shionogi mouse mammary carcinoma SC-3 cell line as an androgen-induced mitogen. We tested if FGF8 was over-expressed in human prostate cancer and if its expression correlated with clinical data and outcome. One hundred and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 14 publications
7
113
0
Order By: Relevance
“…Previous expression studies, including work from our own centre, have assayed total FGF8 levels in clinical material (Leung et al, 1996;Dorkin et al, 1999;Valve et al, 2001). Data concerning FGF8 correlation with clinical parameters, however, have been conflicting and may reflect differences in splice form utilisation (Leung et al, 1996;Tanaka et al, 1998;Dorkin et al, 1999;Valve et al, 2001). Transcript studies of isoform expression are limited by reliance on semiquantitative RT -PCR on heterogeneous frozen materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous expression studies, including work from our own centre, have assayed total FGF8 levels in clinical material (Leung et al, 1996;Dorkin et al, 1999;Valve et al, 2001). Data concerning FGF8 correlation with clinical parameters, however, have been conflicting and may reflect differences in splice form utilisation (Leung et al, 1996;Tanaka et al, 1998;Dorkin et al, 1999;Valve et al, 2001). Transcript studies of isoform expression are limited by reliance on semiquantitative RT -PCR on heterogeneous frozen materials.…”
Section: Discussionmentioning
confidence: 99%
“…These blocks included samples of placenta as well as testis, breast cancer and prostate cancer known to express FGF8 (Tanaka et al, 1998;Dorkin et al, 1999). A dilution of 1 : 500 gave the optimal signals.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies revealed that FGF8b overexpression was found in the majority of prostate cancer (40-80%) (Dorkin et al, 1999;Gnanapragasam et al, 2002Gnanapragasam et al, , 2003Tanaka et al, 2002;Zhong et al, 2006) and breast cancer (B70-100%) . Moreover, its overexpression was clinically associated with disease progression (mainly staging and grading), poor prognosis, poor survival (Dorkin et al, 1999;Valve et al, 2001), and potentially metastasis in prostate cancer (Gnanapragasam et al, 2003;Valta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies revealed that FGF8b overexpression was found in the majority of prostate cancer (40-80%) (Dorkin et al, 1999;Gnanapragasam et al, 2002Gnanapragasam et al, , 2003Tanaka et al, 2002;Zhong et al, 2006) and breast cancer (B70-100%) . Moreover, its overexpression was clinically associated with disease progression (mainly staging and grading), poor prognosis, poor survival (Dorkin et al, 1999;Valve et al, 2001), and potentially metastasis in prostate cancer (Gnanapragasam et al, 2003;Valta et al, 2008). Although the molecular mechanisms for FGF8b overexpression in prostate and breast cancers are not fully understood, the human sex hormone androgen (Tanaka et al, 1992) is known to play a key role, even in the case of breast cancer (Castellano et al, 2010Park et al, 2010 (in addition to prostate cancer (Gnanapragasam et al, 2002)).…”
Section: Introductionmentioning
confidence: 99%